1997
DOI: 10.1001/archneur.1997.00550240035010
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Resonance Imaging Study of Planum Temporale Asymmetry in Men With Developmental Dyslexia

Abstract: These results challenge the notion that anomalous asymmetry of the PT is strongly associated with developmental dyslexia. Given the heterogeneity of the dyslexic population, some subgroup of dyslexic individuals (i.e., those with developmental language disorders) may show unusual symmetry or reversed asymmetry in this region. However, anomalous asymmetry of the planum did not contribute to functional abnormalities demonstrated in these patients by positron emission tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 53 publications
2
57
2
2
Order By: Relevance
“…Functional neuroimaging studies including PET and fMRI have also shown decreased physiological activation in similar regions to both phonological and non-linguistic transient auditory stimuli (e.g. Hagman et al, 1992;Paulesu et al, 1996;Rumsey et al, 1992Rumsey et al, , 1997Shaywitz et al, 1998;Temple et al, 2000). Identification and exploration of the possible etiology and developmental trajectory of such atypical brain organization is of much interest and could be examined within a prospective longitudinal study of infants.…”
Section: Discussionmentioning
confidence: 99%
“…Functional neuroimaging studies including PET and fMRI have also shown decreased physiological activation in similar regions to both phonological and non-linguistic transient auditory stimuli (e.g. Hagman et al, 1992;Paulesu et al, 1996;Rumsey et al, 1992Rumsey et al, , 1997Shaywitz et al, 1998;Temple et al, 2000). Identification and exploration of the possible etiology and developmental trajectory of such atypical brain organization is of much interest and could be examined within a prospective longitudinal study of infants.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizando exames como a ressonância magnética vários autores encontraram em grupos de disléxicos ectopias e microgirias, entre outras alterações corticais em áreas importantes para a audição como a fissura peri-sylviana, áreas de associação do lobo temporal esquerdo, giro angular, giro supramarginal e córtex temporal posterior [21][22][23][24][25][26][27] . P e s t u n 3 re f e re que para a realização de uma leitura com compreensão adequada é necessária a integridade do sistema nervoso periférico e central, bem como certos pré-requisitos fundamentais como atenção seletiva e sustentada, discriminação e perc e p ç ã o auditiva, memória de curto e longo prazo e consciên-cia fonológica, habilidades essas avaliadas no conjunto de testes especiais do PA.…”
Section: Discussionunclassified
“…Generalizing this finding Galaburda et al proposed that symmetrical brains of dyslexics result from a diminished neural loss in the right hemisphere during prenatal development. It deserves mention, however, that more recent MRI techniques have failed to find significant changes in normal planum temporale asymmetry in people with dyslexia [21,39,41]. Variations in subject characteristics (i.e.…”
Section: Introductionmentioning
confidence: 99%